Properties of Cu(In,Ga)Se2 Thin Films and Solar Cells Deposited by Hybrid Process - S. Marsillac; H. Khatri; K. Aryal; R.W. Collins (International Journal of Photoenergy)
Cu(In,Ga)Se2 solar cells were fabricated using a hybrid cosputtering/evaporation process, and efficiencies as high as 12.4% were achieved. The films were characterized by energy-dispersive X-ray spectroscopy, glancing incidence X-ray diffraction, scanning electron microscopy, auger electron spectroscopy, and transmittance and reflectance spectroscopy, and their properties were compared to the ones of films deposited by coevaporation. Even though the films were relatively similar, the ones deposited by the hybrid process tend to have smaller grains with a slightly preferred orientation along the (112) axis and a rougher surface. Both types of films have uniform composition through the depth. Characterization of these films by variable angle of incidence spectroscopic ellipsometry allowed for the calculation of the position of the critical points, via calculation of the second derivative of the dielectric function and fit with critical points parabolic band oscillators. The solar cells were then characterized by current-voltage and quantum efficiency measurements. An analysis of the diode parameters indicates that the cells are mostly limited by a low fill factor, associated mostly with a high diode quality factor (𝐴−1.8) and high series resistance (𝑅𝑠∼1.1 Ω-cm2) .